Business Valuation of Islamic Banks in Merger Plan To Become An Indonesia’s State-Owned Islamic Bank - Khulifa Ahdizia; Dian Masyita; S. Sutisna (ETIKONOMI, 2018)
Indonesia needs a sizeable Islamic bank to confront the ASEAN Economic Community (MEA) in 2020, so it can compete with existing Islamic banks in ASEAN. Then there was a plan to merge several Islamic banks into Government's Islamic banks. This study aims to analyze from the business valuation point of view about the Islamic bank's merger plan in Indonesia and to calculate the value of synergy if the bank merged. Company valuation used DCF-FCFE method and PBV. Islamic banks those were simulated merged are BSM, BRIS, and BNIS. Based on the study there is a synergy when the three banks merged. So, the merger plan of Islamic bank is feasible.DOI: 10.15408/etk.v17i2.7238